A Hierarchical Bipyridine‐Constructed Framework for Highly Efficient Carbon Dioxide Capture and Catalytic Conversion. Issue 6 (22nd December 2016) - Dai, Zhifeng; Sun, Qi; Liu, Xiaolong; Guo, Liping; Li, Jixue; Pan, Shuxiang; Bian, Chaoqun; Wang, Liang; Hu, Xin; Meng, Xiangju; Zhao, Leihong; Deng, Feng; et al.
Abstract: As a C1 feedstock, CO2 has the potential to be uniquely highly economical in both a chemical and a financial sense. Porous materials bearing particular binding and active sites that can capture and convert CO2 simultaneously are promising candidates for CO2 utilization. In this work, a bipyridine‐constructed polymer featuring a high surface area, a hierarchical porous structure, and excellent stability was synthesized through free‐radical polymerization. After metalation, the resultant catalysts exhibited superior activities in comparison with those of their homogeneous counterparts in the cycloaddition of CO2 to epoxides. The high performance of the heterogeneous catalysts originates from cooperative effects between the CO2 ‐philic polymer and the embedded metal species. In addition, the catalysts showed excellent stabilities and are readily recyclable; thus, they are promising for practical utilization for the conversion of CO2 into value‐added chemicals. Abstract : POP star : A bipyridine‐based hierarchically porous organic polymer can capture and convert CO2 simultaneously and exhibits extraordinary performance in CO2 fixation. The materials show excellent stabilities and are readily recyclable.